From Newtonian concepts to a quantum understanding: The evolution of endocrinology and metabolism - Sanjay Kalra,; Saurabh Arora,; Nitin Kapoor, (Journal of the Pakistan Medical Association, 2023)
Conventional endocrinology is based upon linear or Newtonian feedback mechanisms. This framework helps in learning and sharing science in a lucid and simple manner, just as Newton’s Laws clarified our understanding of physics. Modern endocrinology and metabolism are more confusing, as exemplified by the multifarious etiopathogenic factors that continue to be unearthed for various diseases, such as obesity and diabetes. These diseases tend to follow a model similar to that of quantum physics. We propose a Quantum theory of baro-mechanics to help understand the complexity that surrounds metabolic disease, especially obesity. Hopefully, this insight will help mitigate the frustration that one encounters while managing these conditions. Keywords: Bariatric medicine, endocrinology, obesity, pathogenesis, person centred care.